Advokasi Bantuan Hukum bagi Kelompok Rentan Penerima BLT Masa Pandemi Covid-19 dengan Pendekatan PAR di Kabupaten Sidoarjo - Warjiyati, Sri; Salam, Safrin; Wahyuningsih, Yuniar (Proceedings of Annual Conference on Community Engagement, 2022)
Social Assistance in Indonesia is part of the government's efforts to promote economic growth in the time of the pandemic, but it is capable of such abuses as coption, collusion, and nepotism, of course, will cost society. The study was conducted to advocate legal assistance against vulnerable groups during the covid-19 pandemic, the vulnerable groups referred to in the study are the women's community of fishermen in kalanganyar village, district sebindi sidoarjo. It approaches the methods of comparative action research. The solution to the problem offered in this study is how alternative measures to communities of people are vulnerable to uphold commitments, morals, ethics, and example, thereby creating a confident, understanding, and able society to fight for their rights as people who meet the BLT welfare criteria and at the same time foster public trust in government efforts to help BLT.